Tracheostomy with invasive ventilation for ALS patients: Neurologists' roles in the US and Japan. Issue 2 (March 2013) - Rabkin, Judith; Ogino, Mieko; Goetz, Raymond; McElhiney, Martin; Marziliano, Allison; Imai, Takashi; Atsuta, Naoki; Morita, Mitsuya; Tateishi, Takahisa; Matsumura, Tsuyoshi; Mitsumoto, Hiroshi
Abstract Our objective was to determine whether substantial differences in rates of TIV utilization in the U.S. and Japan are associated with the role of the treating neurologist. Questionnaires in English and Japanese were sent to neurologists who treated ALS patients in both countries. Questions included queries about rates of TIV use in their practices, level of encouragement of TIV use, the role of the neurologist in TIV decision making, management of patient/family requests to discontinue TIV once initiated, and personal choices if neurologists themselves had ALS. Results showed that 84% of American neurologists reported fewer than 10% of their patients had TIV, compared to 32% of Japanese. Americans less often encouraged TIV use (79% of American and 36% of Japanese seldom or never suggested or encouraged TIV). Finally, neurologists were asked whether they would choose TIV for themselves in the hypothetical scenario where they had ALS: over 70% of both groups declined TIV for themselves. In conclusion, consistent with past findings, Japanese neurologists were more likely to recommend TIV and more of their patients received TIV. Both groups believed their recommendations influence patient decisions. While Americans seldom recommended TIV to patients and most would not choose TIV for themselves, Japanese neurologists' recommendations and personal choices diverged.